Systematic Literature Review (SLR) : Integrasi Ilmu Pengetahuan dalam Perspektif Filsafat Pendidikan Islam - Khairul Anwar; Salminawati Salminawati; Usiono Usiono (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims to describe how the integration of science in the perspective of Islamic education. The literature study collector starts with a googling search for national and international journals that are relevant to the research to be carried out on previous research through indexed and accredited journalism so that the data collected is valid. The results of research show that Islamic teachings never do a dichotomy between religion and science. In Islam and the philosophers of Islam, the knowledge of religion and general knowledge comes from God. Islam also encourages the whole people to be serious in studying every knowledge. Thoughts about integration or Islamization of science today are much done by Muslim intellectuals. Overall, this is done in the midst of a busy global world filled with advances in science and technology. With the concept that the Muslims will advance, they can chase behind the Westerners if they are able to transform and absorb science effectively. Furthermore, it is assumed that science originating in Western countries is considered secular so that it must be rejected, or at least interpreted and translated with Islamic understanding and reinforced from a philosophical point of view.